(3aVGFd GdNdaGA GdGQHYI hZjQge hjdjg GdGeGeI hGdQO Ydi GdQGaVI (B/s - (3GHj fYje GdCUHgGfj, GMeO Hf YHOGddg,s 948-1038 (Beirut : Dar al-Kutub al-'Ilmiyah, 2003)
Edition of a classic work on the virtues & qualities of the first four Caliphs, with annotations on the hadith sources
Keywords: Caliphs in the Hadith